Comparison of Gray Matter Atrophy in Behavioral Variant Frontal Temporal Dementia and Amyotrophic Lateral Sclerosis: A Coordinate-Based Meta-Analysis - Luo, Chunyan; Hu, Na; Xiao, Yuan; Zhang, Wenjing; Gong, Qiyong; Lui, Su (Frontiers in Aging Neuroscience, 2020)
Background: There is growing evidence supporting behavioral variant frontotemporal dementia (bvFTD) and amyotrophic lateral sclerosis (ALS) as extreme points of a disease spectrum. The aim of this study was to delineate the common and different patterns of grey matter atrophy associated with bvFTD and with ALS by pooling together the results of previous voxel-based morphometry (VBM) studies. Methods: We retrieved VBM studies that investigated grey matter atrophy in bvFTD patients versus controls and in ALS patients versus controls. Stereotactic data were extracted from those studies, and subsequently tested for convergence and difference using activation likelihood estimation (ALE). Behavioral decoding using the BrainMap database was used to assess the functional roles of the regions affected by bvFTD and/or ALS Results: Our study demonstrated a convergence of grey matter atrophy in frontolimbic structures involving bilateral anterior insula and anterior cingulate cortex, bilateral caudate and left anterior insula in bvFTD, and higher degree of atrophy in the right motor cortex in ALS. Behavioral decoding analysis revealed that the pattern of the affected regions contributed to the dysfunction of emotional and cognitive processing in bvFTD, and dysfunction of motor execution in ALS. Conclusion: Our results revealed a shared neural basis between bvFTD and ALS, as well as specific and distinct neural signature that underpinned the clinical manifestations of those two disease. Those findings outlined the role of frontomedical-candate network in the development of bvFTD-like deficits in ALS patients.